STUDİES ON THE COOPERATİVE SYSTEM İN TURKEY: A CONTENT ANALYSİS (Third Sector Social Economic Review, 2022)
The purpose of the present study was to examine the articles on cooperatives conducted in Turkey between 2010 and 2021 according to some variables and to determine the current situation of what kind of trend research is showing from a holistic perspective. In this context, 120 articles that were scanned in Ulakbilim and Dergipark databases about cooperatives or cooperative system in the title and keywords were analyzed. Articles, distribution by years, study method, type of cooperatives, fields of study, published journals, sources used, number of pages and averages of page numbers, keywords, number of authors, titles of authors, universities at which the authors were working, departments and genders of the authors were analyzed in this respect. As a result of the study, it was found that the number of studies conducted in the field of cooperative system started to increase as of 2016, most of the studies were empirical studies, and studies in different fields in many types of cooperatives were published in many different journals. With this study, it is considered that future articles in the field of cooperatives will guide researchers in determining the types of cooperatives, study subjects, in terms of contents and shape.
Keywords: Cooperative; Cooperative System; Agricultural Economics; Content Analysis; Agricultural Cooperative System